Radical recognition: a border criminology theory of justice - Barker, Vanessa (Handbook on border criminology, 2024)
This chapter develops a normative and sociological framework of justice based on a synthesis of border criminologies scholarship. A Border Criminology theory of justice entails three pillars: (1) respect for persons or radical recognition; (2) the principles of nonviolence; and (3) civic engagement.